2018
DOI: 10.1111/bjh.15556
|View full text |Cite
|
Sign up to set email alerts
|

Lower prevalence of subsegmental pulmonary embolism after application of the YEARS diagnostic algorithm

Abstract: SummaryThe rate of identified isolated subsegmental pulmonary embolism (ssPE) has doubled with advances in computed tomography pulmonary angiography (CTPA) technology, but its clinical relevance is debated. The YEARS diagnostic algorithm was shown to safely reduce the number of required CTPAs in the diagnostic management of PE. We hypothesized that the higher threshold for performing CTPA in YEARS was associated with a lower prevalence of ssPE compared to the conventional diagnostic algorithm. We compared 2291… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…32 Conversely, diagnostic strategies raising the threshold for performing CTPA in the setting of suspected PE are associated with a lower prevalence of ssPE. 33,34 Based on these findings, the latest guidelines of the American College of Chest Physicians have suggested that in patients with ssPEs and no proximal DVT in the legs who have a low risk for recurrent VTE, clinical surveillance is preferred over anticoagulation. 35 Definite evidence for the safety of such an approach has yet to arrive from a prospective single-arm trial (NCT01455818) and a planned randomized controlled trial (NCT04263038).…”
Section: Discussionmentioning
confidence: 99%
“…32 Conversely, diagnostic strategies raising the threshold for performing CTPA in the setting of suspected PE are associated with a lower prevalence of ssPE. 33,34 Based on these findings, the latest guidelines of the American College of Chest Physicians have suggested that in patients with ssPEs and no proximal DVT in the legs who have a low risk for recurrent VTE, clinical surveillance is preferred over anticoagulation. 35 Definite evidence for the safety of such an approach has yet to arrive from a prospective single-arm trial (NCT01455818) and a planned randomized controlled trial (NCT04263038).…”
Section: Discussionmentioning
confidence: 99%
“…Trials such as ADJUST -PE (Age-adjusted D-dimer Cutoff Levels to Rule Out Pulmonary Embolism), YEARS (Simplified diagnostic management of suspected pulmonary embolism), PROPER (Pulmonary Embolism Rule-Out Criteria on Subsequent Thromboembolic Events Among Low-Risk Emergency Department Patients), and PEGeD (Pulmonary Embolism Graduated D-dimer) allow clinicians to significantly decrease the use of diagnostic imaging (ie, CTPA) in patients with a lower C -PTP of having PE. [85][86][87][88] A post hoc analysis of data from 2 prospective studies assessed the prevalence of SSPE in a cohort managed with the YEARS criteria and compared it with the prevalence in a cohort managed with a standard diagnostic strategy. 23,86 The prevalence of SSPE was 10% and 16% in the 2 cohorts, respectively (absolute difference, 6%; 95% CI, 1.4-10).…”
Section: Outcomes Of Patients With Subsegmental Pulmonarymentioning
confidence: 99%
“…The clinical significance of these subsegmental PE (ssPE) and the need to treat with anticoagulation is also debatable (Carrier & Klok, 2017). In this month's journal the utility of the YEARS algorithm is further evaluated (van der Pol et al, 2018). In a post-hoc analysis of the original YEARS study, van der Pol et al (2018)compared the number of patients undergoing CTPA (48%) with those in the Christopher study (68%) an earlier prospective PE outcome study performed in the same Dutch hospitals as the YEARS study (van Belle et al, 2006;van der Hulle et al, 2017).…”
Section: Editorial Commentmentioning
confidence: 99%
“…In this month's journal the utility of the YEARS algorithm is further evaluated (van der Pol et al, 2018). In a post-hoc analysis of the original YEARS study, van der Pol et al (2018)compared the number of patients undergoing CTPA (48%) with those in the Christopher study (68%) an earlier prospective PE outcome study performed in the same Dutch hospitals as the YEARS study (van Belle et al, 2006;van der Hulle et al, 2017). In the YEARS study group PE was identified in 12% (n = 278) of those who underwent imaging, of whom only 28 patients (10% of all PEs diagnosed) were subsegmental.…”
Section: Editorial Commentmentioning
confidence: 99%
See 1 more Smart Citation